Recent Progress in Electrochemiluminescence of Halide Perovskites - Cao, Yue; Zhu, Jun-Jie (Frontiers in Chemistry, 2021)
Halide perovskites are a rapidly developing class of solution-processable semiconductors which, to date, have a huge impact across several scientific communities. The remarkable photophysical attributes of halide perovskites illustrate their considerable potential in the electrochemiluminescence (ECL) realm. Over the past 4 years, great progress has been achieved in using halide perovskites as ECL emitters. In this mini-review, the basic characteristics, synthetic approaches, and ECL mechanisms for halide perovskite emitters are first introduced. To the best of our knowledge, most of the reported ECL-active halide perovskites and their disclosed unique features are detailly summarized. Stabilization and interface manipulation strategies for desirable ECL performance are further highlighted. The preliminary halide perovskites-related ECL applications are finally discussed, and prospects are also anticipated.